2005
DOI: 10.1063/1.1982787
|View full text |Cite
|
Sign up to set email alerts
|

Predicting atomic dopant solvation in helium clusters: The MgHen case

Abstract: We present a quantum Monte Carlo study of the solvation and spectroscopic properties of the Mg doped helium clusters MgHen with n = 2 − 50. Three high level (MP4, CCSD(T) and CCSDT) MgHe interaction potentials have been used to study the sensitivity of the dopant location on the shape of the pair interaction. Despite the similar MgHe well depth, the pair distribution functions obtained in the diffusion Monte Carlo simulations markedly differ for the three pair potentials, therefore indicating different solubil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(110 citation statements)
references
References 46 publications
13
97
0
Order By: Relevance
“…The typical distance between the impurity and the center-of-mass of the droplet decreases as the impurity becomes fully solvated. Our results thus confirm those of Mella et al 14 Finally, we have employed the pure estimator to determine the radial structure for the isotopically pure N 4 = 8 and 30 droplets. We have found that the differences between pure and mixed estimators of the radial densities are very small and not worth to be plotted.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The typical distance between the impurity and the center-of-mass of the droplet decreases as the impurity becomes fully solvated. Our results thus confirm those of Mella et al 14 Finally, we have employed the pure estimator to determine the radial structure for the isotopically pure N 4 = 8 and 30 droplets. We have found that the differences between pure and mixed estimators of the radial densities are very small and not worth to be plotted.…”
Section: Methodssupporting
confidence: 76%
“…Within Density Functional Theory (DFT), it has been found to solvate in 3 He droplets and to be very delocalized in 4 He ones. 10,13 Previous diffusion Monte Carlo calculations (DMC) 14 have yielded the result that Mg is fully solvated for a critical number of 4 He atoms of about N 4 = 30. A similar transition from surface to bulk location of Mg was also found within DFT.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, variational ͑VMC͒ and DMC are much simpler in flat manifolds. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] The works we have cited are applications of VMC and DMC to clusters in Cartesian coordinates, and constitute only a small sample of the most recent investigations. On the other hand, diffusion in manifolds remains a topic of research in pure mathematics as well as mathematical physics.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this bulk location, the Ca@ 3 He 40 cluster is not spherically symmetric. This also happens for clusters doped with other weakly attractive impurities, such as Mg in small 4 He clusters [38]. The reason is the tendency of the system to have a helium density as close as possible to its liquid value in order to maximize its binding.…”
Section: Resultsmentioning
confidence: 99%
“…than can be interpreted as the negative of the He evaporation energies [38]. We have plotted −∆(N 3 ) in Fig.…”
Section: Resultsmentioning
confidence: 99%